Sistema de inferencia difusa secuencial basado en aritmética distribuida - Olea Salgado, David Camilo; Gaona Barrera, Andrés Eduardo; Melgarejo Rey, Miguel Alberto (Ingeniería, 2008)
This article presents the design and validation of a Mamdani type hardware fuzzy inference system with two inputs, 16 rules and one output. Fuzzy inference engine of this system works sequentially in order to optimize hardware resources. Defuzzification stage is novel due to it is based on a distribute arithmetic approach. Systemss architecture can be modified by means of a high level software tool.